2017
DOI: 10.3389/fimmu.2017.00912
|View full text |Cite
|
Sign up to set email alerts
|

Altered N-Linked Glycosylation in Follicular Lymphoma and Chronic Lymphocytic Leukemia: Involvement in Pathogenesis and Potential Therapeutic Targeting

Abstract: B-cell antigen receptor (BCR) expression is indispensable for survival of most B-cell malignancies. In follicular lymphoma (FL), N-linked glycosylation sites are introduced in the immunoglobulin (Ig) variable region genes. Oligosaccharides added to the acquired sites are unusually of the high-mannose type. These glycans interact with mannose-specific lectins, especially with dendritic cell-specific intercellular adhesion molecule-3-grabbing non-integrin (DC-SIGN). Lectin binding to FL triggers persistent activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 57 publications
0
13
0
1
Order By: Relevance
“…Candidate molecules for this interaction include C-type lectins expressed by macrophages and dendritic cells, which have been proposed as possible targets for new therapeutic strategies. In this regard, promising agents include both antibodies against high-mannose glycans and mannose-based oligosaccharide mimics or non-carbohydrate glycomimetics that act as competitive inhibitors of lectin–glycoprotein interactions are currently being developed against human immunodeficiency virus, since envelope glycans of this virus are almost entirely of the oligomannose type ( 12 ). Further studies are needed to validate the efficacy of these therapeutics in the treatment of FL.…”
Section: Early Steps In Lymphomagenesismentioning
confidence: 99%
“…Candidate molecules for this interaction include C-type lectins expressed by macrophages and dendritic cells, which have been proposed as possible targets for new therapeutic strategies. In this regard, promising agents include both antibodies against high-mannose glycans and mannose-based oligosaccharide mimics or non-carbohydrate glycomimetics that act as competitive inhibitors of lectin–glycoprotein interactions are currently being developed against human immunodeficiency virus, since envelope glycans of this virus are almost entirely of the oligomannose type ( 12 ). Further studies are needed to validate the efficacy of these therapeutics in the treatment of FL.…”
Section: Early Steps In Lymphomagenesismentioning
confidence: 99%
“…We have recently demonstrated that FL-FDC niche promotes, via the secretion of CCL2 and CSF-1, monocyte recruitment, differentiation, and polarization towards an M2-like pro-tumoral phenotype, as seen in FL patient biopsies [5], favoring angiogenesis, dissemination, and immunosuppression [22]. Moreover, macrophages express C-type lectin dendritic cell-specific intercellular adhesion molecule-3-grabbing non-integrin (DC-SIGN) that binds to mannosylated BCR, activating B cell survival independently of Ag [23][24][25]. In addition, monocyte/macrophages trans-present IL-15 to B cells in the FL niche and cooperate with T-cell-derived CD40L to promote IL-15-dependent B-cell proliferation [26].…”
Section: Fl Microenvironment: Friend or Foe?mentioning
confidence: 99%
“…In contrast to the highly sialylated variable domain glycans in RA, AAV, and IgG4-RD patients, FL variable domain glycans were reported to be rich in high-mannose structures ( Table 1) (91,92,103). Such glycans were solely observed at sites which were newly acquired through somatic hypermutation.…”
Section: Composition Of the Glycanmentioning
confidence: 99%